Forage Production of Hay-Type Sorghum Cultivars - J. L. Moyer; J. D. Holman (Kansas Agricultural Experiment Station Research Reports, 2016)
Forage production was measured from three cuttings of 14 hay-type sorghum-sudan entries. Total annual yield was greater from ‘AS5201’, ‘Sweet Sioux WMR’, and ‘AS9302’ than from five lower-yielding cultivars.
Keywords: pastures; hay